Filmic-dialectal frustration in the world of Almodóvar: Approaches and Analysis of the Subversive Untranslatability in Two 1980s’ Feature Films by Pedro Almodóvar - Macarro, Jordi (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In the context of the last quarter of the 20th century in Spain, cinema played an important role in the subversive process of a society that was awakening from its dictatorial lethargy to cope with European cultural modernity. We can find evidence of this process in the first feature films by the Spanish director Pedro Almodóvar. They capture a transgressive contemporary imaginary, both visual and lexical, that the French-language subtitles dilute and even make disappear, generating a subversive frustration resulting from the untranslatability of the original audio-visual component.